(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the teratogenicity of Vitamin A excess on intrauterine development of thymus in albino rats. Study Design: Experimental study Place and Duration of Study: This study was conducted at the Department of Anatomy/ Histopathology, Shaikh Zayed Postgraduate Medical Institute, Lahore from September 2008 to September 2009. Materials and Methods: Study was conducted with 18 pregnant female albino rats, of Sprague-dawley variety. These female rats were randomly separated into equal groups, A, B and C (n=6). Vitamin A was used in the form of Isotretinoin (13-cis retinoic acid). The dose of isotretinoin used in this study was constant i.e, 2.5mg/kg body weight of rats for every experimental group. Taking the trimester of pregnancy as variable of the study dose was given on 9 (mid trimester) and 17 (late trimester) days of pregnancy to the mother rats. The sample size was obtained by collecting 18 foetuses from each group. Thymuses were collected from the rat foetuses of each group after dissection. Results: The foetuses of experimental group whose mother rats received the dose of Vitamin A in mid trimester showed thymic ectopia in a significant number of foetuses (P<0.01), while dose of Vitamin A given in late trimester caused thymic hypoplasia (P<0.01) in fetuses of albino rats. Conclusion: It is obvious with these findings that single dose of Vitamin A can cause deleterious effects on developing thymus in albino rats. Recommendations: Caution must be taken while administration of Vitamin A to a pregnant woman.